Uji Efektivitas Ekstrak Etanol Kulit Jagung (Zea mays L.) Sebagai Antihiperglikemia Pada Mencit (Mus musculus L.) Yang Diinduksi Sukrosa - Manuppak Irianto Tampubolon; Devina Chandra; Kesaktian Manurung (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Hyperglycemia is a metabolic disorder characterized by elevated blood glucose levels and serves as a primary risk factor for diabetes mellitus and its associated complications, including cardiovascular disease, nephropathy, neuropathy, and retinopathy. Corn husk (Zea mays L.) contains flavonoid compounds that exhibit antihyperglycemic activity through inhibition of α-amylase and α-glucosidase enzymes. Objective: This study aimed to identify the presence of flavonoids in corn husk simplicia and evaluate the antihyperglycemic effectiveness of corn husk ethanol extract in sucrose-induced male mice (Mus musculus L.). Methods: An experimental design was employed using 25 male mice randomly assigned into five treatment groups (n=5): negative control (0.5% Na-CMC), positive control (glibenclamide 0.013 mg/20 g BW), and corn husk ethanol extract at concentrations of 10%, 20%, and 40% (equivalent to 500, 1000, and 2000 mg/kg BW, respectively). Hyperglycemia was induced by oral administration of sucrose solution at a dose of 0.81 g/20 g BW. Fasting blood glucose levels were measured at 0, 30, 60, 90, and 120 minutes using a glucometer. Phytochemical screening was performed to detect flavonoid compounds. Data were analyzed using One-Way ANOVA followed by Tukey HSD post-hoc test (α=0.05). Results: Phytochemical screening confirmed the presence of flavonoids in the ethanol extract. Statistical analysis revealed that extract concentrations of 10% and 20% did not produce significant antihyperglycemic effects (p>0.05). In contrast, the 40% concentration significantly reduced fasting blood glucose levels compared to the negative control (p=0.049), with a percentage reduction of 42.50% at 120 minutes. The glucose-lowering effect of the 40% extract was comparable to that of the glibenclamide positive control (p=0.821). Conclusion: Corn husk ethanol extract demonstrates antihyperglycemic potential in sucrose-induced mice, with the 40% concentration exhibiting the most effective glucose-lowering activity, comparable to glibenclamide. Further studies are warranted to elucidate the molecular mechanisms and conduct clinical trials in humans.